Analisis Kepuasan Administrasi Akademik dan Kinerja Dosen Terhadap Loyalitas Mahasiswa Fakultas Ekonomi Universitas Negeri Medan - Nura, Alfi; Lubis, Sapriani Nur Adilah; Natasya, Melinda; Nasution, Dewi Amanda; Anggraini, Dwi Aulia; Daulay, Riski (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the satisfaction with academic administrative services and lecturer performance, as well as their impact on student loyalty at the Faculty of Economics, Universitas Negeri Medan. The research employed a qualitative method involving 20 students as respondents. Each student completed a form containing open-ended questions based on indicators of each research variable. The results showed that most students were satisfied with academic administrative services, particularly in terms of ease of information access and the professional attitude of administrative staff. Lecturer performance was also rated positively, especially in mastering the subject matter, using engaging teaching methods, and openness to discussion. Student loyalty was reflected in their desire to complete their studies at the faculty, a sense of pride, and willingness to recommend the faculty to others. However, the speed of administrative services and lecturers' responsiveness to student inquiries still need improvement. These findings indicate that satisfaction with academic administrative services and lecturer performance contributes positively to the level of student loyalty toward the institution.